Predictors of Sexual Minority Youth's Reported Suicide Attempts and Mental Health. Issue 6 (12th May 2017) - Puckett, Jae A.; Horne, Sharon G.; Surace, Francisco; Carter, Alice; Noffsinger-Frazier, Nicole; Shulman, Julie; Detrie, Pam; Ervin, Audrey; Mosher, Chad
ABSTRACT: Lesbian, gay, and bisexual youth (LGBY) report higher rates of mental health concerns compared to heterosexual youth due to minority stressors. This study examined the interpersonal and intrapersonal variables that predict psychological distress and self-reported suicide attempts in a sample of 61 LGBY in the Mid-South, which is a highly overlooked regional area for LGBY research. Youth who lost friends when coming out were 29 times more likely to report suicide attempts, and those who experienced psychological maltreatment from caregivers were 9.5 times more likely to report a suicide attempt. Internalized heterosexism, feelings of guilt or shame, and psychological maltreatment from caregivers were significant predictors of depression and anxiety symptoms. This study highlights the importance of creating affirming spaces for LGBY, particularly in areas of the country that experience greater political oppression of sexual minorities, such as the Mid-South.